Corporate Finance, Financial Development, and Growth - Bebczuk, Ricardo Néstor (1999)
While there is consensus in that financial development exerts a positive effect on growth, the identification of the actual transmission channels is much less clear. Our work intends to contribute evidence on the role of the financial system in overcoming informational asymmetries. Starting from the observation that internal funds (retained earnings plus depreciation) are the primary source of funds in most countries, we use a simple growth model with asymmetric information to show that the proportion of private investment financed with bank credit is positively associated to growth. After controlling for some factors, this ratio may be used as a proxy for the extent of (directly unobservable) informational asymmetries. Applying a dynamic panel data technique on a cross-country database we find empirical support for the model.